2018
DOI: 10.1038/s41419-018-1112-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide-induced TFEB nuclear translocation enhances mitophagy/mitochondrial biogenesis in hepatocytes and ameliorates inflammatory liver injury

Abstract: Carbon monoxide (CO) can confer protection against cellular stress, whereas the potential involvement of autophagy and lysosomal biogenesis remains incompletely understood. We demonstrate here that the activation of protein kinase R (PKR)-like endoplasmic reticulum (ER) kinase (PERK) with CO increased the nuclear translocation of transcription factor EB (TFEB). PERK activation by CO increased intracellular Ca2+ concentration and the phosphatase activity of calcineurin against TFEB. Moreover, we found that in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 46 publications
3
68
0
1
Order By: Relevance
“…Interestingly, the activities of both Nrf2 and TFEB were shown to be downregulated in DKD (Xiao et al, 2017;Zhao et al, 2018). With increasing evidence supporting the role of TFEB during mitophagy (Kim et al, 2018;Tan et al, 2019), the involvement of crosstalk between TFEB and Nrf2 in this process should be further investigated.…”
Section: Mitophagy and Dkdmentioning
confidence: 96%
“…Interestingly, the activities of both Nrf2 and TFEB were shown to be downregulated in DKD (Xiao et al, 2017;Zhao et al, 2018). With increasing evidence supporting the role of TFEB during mitophagy (Kim et al, 2018;Tan et al, 2019), the involvement of crosstalk between TFEB and Nrf2 in this process should be further investigated.…”
Section: Mitophagy and Dkdmentioning
confidence: 96%
“…HO-1, HO-1-derived bilirubin, biliverdin, and CO have been shown to have antioxidative and anti-inflammatory properties 11,20 . Furthermore, HO-1 and CO, which can be increased by ALA/SFC, have been shown to increase mtDNA copy number by enhanced protein expression of nuclear respiratory factor-1 (NRF1), peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC1α), and mitochondrial transcriptional factor A (TFAM) 8,14,21,22 . In this study, we observed that ALA/SFC upregulated mtDNA copy number, as well as HO-1 mRNA and protein in normal and patient-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…CO reduces the number of neutrophils in septic lungs by controlling transendothelial migration ( Mizuguchi et al., 2009 ). Moreover, at low concentrations, CO attenuates the lung inflammatory response in mice challenged with LPS or live bacteria ( Macgarvey et al., 2012 ; Wegiel et al., 2014b ; Wilson et al., 2017 ; Kim et al., 2018 ). It differentially and selectively inhibits LPS-induced expression of pro-inflammatory cytokines (e.g., TNF-α, IL-6), while increasing levels of anti-inflammatory molecules (e.g., IL-10, IL-1 receptor antagonist (IL-1Ra, PPAR - γ) ( Bilban et al., 2006 ; Haschemi et al., 2011 ; Piantadosi et al., 2011 ; Macgarvey et al., 2012 ; Uddin et al., 2015 ).…”
Section: Co Anti-inflammatory and Antioxidant Functions And Relevancmentioning
confidence: 99%
“…This may be a key mechanism in CO’s modulation of the MΦ response to infections. CO also induces mitochondrial and lysosomal biogenesis by activating the guanylate cyclase and the PI3K/AKT pathway, and upregulating transcription factors such as Nrf1, Transcription Factor A, mitochondrial (TFAM), Nrf2, Transcription Factor EB (TFEB), and PGC-1α ( Zuckerbraun et al., 2007 ; Piantadosi et al., 2011 ; Queiroga et al., 2012 ; Wegiel et al., 2013 ; Motterlini and Foresti, 2017 ; Kim et al., 2018 ). These data suggest that cellular CO primes MΦs to better respond to cellular stressors.…”
Section: Co Stimulates Cellular Host Defense Against Infections: Implmentioning
confidence: 99%